2022
DOI: 10.3389/fmars.2022.1014336
|View full text |Cite
|
Sign up to set email alerts
|

Response of the metabolic and autophagy pathways in Mytilus under starvation

Abstract: Being an industrially valuable species of bivalve, Mytilus is widespread in the area around the eastern coast of China. Starvation is an environmental stress that mussels often encounter in their growth. However, few report carried out on the physiological and biochemical response and molecular regulation and adaptation mechanism of mussels under starvation. To illustrate the molecular mechanism of hosts of Mytilus to starvation, the gill transcriptome was used for analysis before and after 9 days of starvatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…According to the GO functional annotation analysis, mussel cilia activity and motile cilia cell activity are significantly enriched in downregulated proteins (e.g., TEKT1). Furthermore, starvation has been shown to induce ciliated cell autophagy and inhibit primary cilia formation ( Xie et al, 2022 ). The inhibition of primary cilia formation is also a sign of energy conservation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the GO functional annotation analysis, mussel cilia activity and motile cilia cell activity are significantly enriched in downregulated proteins (e.g., TEKT1). Furthermore, starvation has been shown to induce ciliated cell autophagy and inhibit primary cilia formation ( Xie et al, 2022 ). The inhibition of primary cilia formation is also a sign of energy conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Starvation stress is a frequent environmental stressor in mussel growth and is associated with cultivation patterns (no artificial feeding), intraspecific competition, the unequal seasonal and spatial distribution of food and environmental changes (Bayne, 1973;Xie et al, 2022). In addition, in our previously study, we found that M. coruscus were tolerant to starvation, and no mortality occurred after 9 days of starvation (Xie et al, 2022). According to literature, most bivalves have a strong tolerance to starvation, such as Pinctada martensi could survival at least 12 days under starvation (He et al, 2010), and Lamellidens marginalis can tolerate 32 days starvation and adapted to maintain a stable immune profile during starvation (Mahapatra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation